If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 = 5n + 7 + -1(3n) Remove parenthesis around (3n) 19 = 5n + 7 + -1 * 3n Multiply -1 * 3 19 = 5n + 7 + -3n Reorder the terms: 19 = 7 + 5n + -3n Combine like terms: 5n + -3n = 2n 19 = 7 + 2n Solving 19 = 7 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 19 + -2n = 7 + 2n + -2n Combine like terms: 2n + -2n = 0 19 + -2n = 7 + 0 19 + -2n = 7 Add '-19' to each side of the equation. 19 + -19 + -2n = 7 + -19 Combine like terms: 19 + -19 = 0 0 + -2n = 7 + -19 -2n = 7 + -19 Combine like terms: 7 + -19 = -12 -2n = -12 Divide each side by '-2'. n = 6 Simplifying n = 6
| 6x-10y+6=0 | | 3(x+4)/4=x+7 | | 9/14-1/14 | | .5(6x-4)=2x+3-5+x | | 12x-11-x^2=0 | | (2x-3)+x=90 | | 2/7*2/3 | | 8x-24x=4 | | 3x+29=7x-34 | | 2x-23=-11+8x | | 16i/1+i | | 3x+29=7x-43 | | 3r-11=-51+8r | | 60=27x+18 | | 6x+90+8x+20=180 | | 4x^2+14x+21=3x^2-6 | | X-9x+19=0 | | 3x+29=7x-4 | | 10x-6x+4=26 | | 5x-6(8x-10)=17 | | 243-67+92=7 | | 165x-33y=33 | | t=3+10x | | Q-3PR=2R | | 8=10-m | | 7(-x+3)=-7-21 | | 2x/x+3=-6/x+3 | | 14x-20=-64 | | 8x-2(0)=16 | | 3p/7+14=8 | | 2x^1/2 | | -4(3m+5)=-2(m+5) |